Pembuatan Geomapping Tata Letak Usaha Micro Menenga Kecil Desa Sebani - Wahyudi Wahyudi; Didin Sirojudin; Khoirun Nisa'; Moh Faridl Darmawan; Elok Fadilatul Fajria; Nanda Ade Fahreza; Siti nurul hidayati aurelia putri wijaya (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
In today's digital age, the need for easily accessible information is essential. One of the efforts that can be made is to make a geomapping map of the layout of small micro businesses in Menenga village, with this information board, the village community and outside parties can easily find the existence of small micro businesses in order to help increase the visibility of small micro businesses, increase the attractiveness of the village, and encourage local economic growth. The approach method used in this activity is Participatory Action Research. This method emphasizes the active involvement of the community, village officials, and small and medium-sized micro business actors in every stage of activities, starting from problem identification, planning, implementation, to evaluation of results. This approach was chosen because it is in accordance with the main goal of the program, which is to empower village communities in the use of geomapping to support the promotion of micro, small and medium-sized enterprises in a sustainable manner. By directly involving the community, it is hoped that they can understand, master, and continue the management of micro and small and medium-sized business data independently in the future. Through this activity, a database of small and small micro businesses has been produced, digital geomapping maps, and banners of small micro businesses that are installed on village information boards. These results make it easier for the public and visitors to access information, as well as being an effective means of promotion for small and medium-sized micro business actors.